Perilaku Etnis Batak Toba Dalam Pemilukada Kota Medan Tahun 2010 - Nova A. Malau (Dinamika Politik, 2012)
This research is a study about the behavior of Toba ethnic in electing the regent of Medan. The focus is examining about the factors which influence Toba society at Binjai District in deciding the selection candidate. The finding of this research among others there are three factors which influence society in electing the candidate of mayor. First, characteristic and  perspective with mission of the couple candidates. Second, the background of party which carries the candidate. Third, influence from  association or group of ethnic. The method which is used is the descriptive-qualitative method that is intend to describe an event more detail.Key Words : Behavior of politic, political grouping, general elections